Protein unfolding as a switch from self-recognition to high-affinity client binding - Bastian Groitl (Nature Portfolio, 2016)
Under stress conditions the molecular chaperone Hsp33 is activated to process unfolded proteins. Here, the authors use in vivo and in vitro crosslinking and 19F-NMR to elucidate the binding site for misfolded proteins and are able to propose a model for its mechanism of action.